Ozone depletion and climate change: Impacts on UV radiation. - McKenzie, Richard L.; Aucamp, Pieter J.; Bais, Alkiviades F.; Björn, Lars Olof; Ilyas, Mohamad; Madronich, Sasha (Photochemical & Photobiological Sciences, 2011)
The Montreal Protocol is working, but it will take several decades for ozone to return to 1980 levels. The atmospheric concentrations of ozone depleting substances are decreasing, and ozone column amounts are no longer decreasing. Mid-latitude ozone is expected to return to 1980 levels before mid-century, slightly earlier than predicted previously. However, the recovery rate will be slower at high latitudes. Springtime ozone depletion is expected to continue to occur at polar latitudes, especially in Antarctica, in the next few decades. Because of the success of the Protocol, increases in UV-B radiation have been small outside regions affected by the Antarctic ozone hole, and have been difficult to detect. There is a large variability in UV-B radiation due to factors other than ozone, such as clouds and aerosols. There are few long-term measurements available to confirm the increases that would have occurred as a result of ozone depletion. At mid-latitudes UV-B irradiances are currently only slightly greater than in 1980 (increases less than ~5%), but increases have been substantial at high and polar latitudes where ozone depletion has been larger. Without the Montreal Protocol, peak values of sunburning UV radiation could have been tripled by 2065 at mid-northern latitudes. This would have had serious consequences for the environment and for human health. There are strong interactions between ozone depletion and changes in climate induced by increasing greenhouse gases (GHGs). Ozone depletion affects climate, and climate change affects ozone. The successful implementation of the Montreal Protocol has had a marked effect on climate change. The calculated reduction in radiative forcing due to the phase-out of chlorofluorocarbons (CFCs) far exceeds that from the measures taken under the Kyoto protocol for the reduction of GHGs. Thus the phase-out of CFCs is currently tending to counteract the increases in surface temperature due to increased GHGs. The amount of stratospheric ozone can also be affected by the ...